P485 Apolipoprotein C3 is Downregulated in Patients with Inflammatory Bowel Disease. (21st January 2022) - Hernandez Camba, A; Carrillo Palau, M; Ramos, L; Alonso, I; Vela, M; Hernández, A; Arranz, L; Hernández, N; Hernández-Guerra, M; Ferráz, I
Abstract: Background: Inflammatory bowel disease (IBD) has been associated with an abnormal lipid profile. Apolipoprotein C3 (ApoC3) is a key molecule of triglycerides metabolism that is known to be related to inflammation and cardiovascular (CV) disease. In the present study, we aim to study if ApoC3 serum levels differ between patients with IBD and controls, and if the hypothetical disturbance of ApoC3 can be explained by IBD characteristics. Methods: Cross-sectional study that included 405 individuals, 197 patients with IBD and 208 age- and sex-matched controls. ApoC3 and standard lipid profiles were assessed in patients and controls. A multivariable analysis was performed to analyze whether ApoC3 serum levels were altered in IBD and to study their relationship to IBD characteristics. Results: After fully multivariable analysis including CV risk factors, use of statins, and changes in the lipid profile caused by the disease itself, patients with IBD showed significant lower serum levels of ApoC3 (beta coef. -1.6 [95%CI -2.5- -0.7] mg/dl, p=0.001). Despite this, inflammatory markers, disease phenotypes or disease activity of IBD were not found to be responsible for this downregulation. Conclusion: Apolipoprotein C3 is downregulated in patients with IBD.